1, 4, 5, 8-Naphthalenetetracarboxylic dianhydride grafted phthalocyanine macromolecules as an anode material for lithium ion batteries. Issue 11 (21st April 2021) - Tao, Lihong; Zhao, Jianjun; Chen, Jun; Ou, Caixia; Lv, Weixia; Zhong, Shengwen
Abstract : A large-volume branched phthalocyanine conjugated TNTCDA-NiPc that is electrolyte-stable with many active sites was synthesized. The capacity, cycling stability, rate capability of TNTCDA-NiPc electrode are greatly improved compared with NTCDA electrode. Abstract : For solving the problems of high solubility in electrolytes, poor conductivity and low active site utilization of organic electrode materials, in this work, 1, 4, 5, 8-naphthalenetetracarboxylic dianhydride (NTCDA ) grafted nickel phthalocyanine (TNTCDA-NiPc ) was synthesized and used as an anode material for lithium ion batteries. As a result, the dispersibility, conductivity and dissolution stability are improved, which is conducive to enhancing the performance of batteries. The initial discharge capacity of the TNTCDA-NiPc electrode is 859.8 mA h g −1 at 2 A g −1 current density, which is much higher than that of the NTCDA electrode (247.4 mA h g −1 ). After 379 cycles, the discharge capacity of the TNTCDA-NiPc electrode is 1162.9 mA h g −1, and the capacity retention rate is 135.3%, which is 7 times that of the NTCDA electrode. After NTCDA is grafted to the phthalocyanine macrocyclic system, the dissolution of the NTCDA in the electrolyte is reduced, and the conductivity and dispersion of the NTCDA and phthalocyanine ring are also improved, so that more active sites of super lithium intercalation from NTCDA and phthalocyanine rings are exposed, which results in better electrochemical performance. The strategy of grafting small molecular active compounds into macrocyclic conjugated systems used in this work can provide new ideas for the development of high performance organic electrode materials.